Implementasi Pendidikan Kewanitaan di Perguruan Tinggi Pesantren - Ach. Nurholis Majid (Universitas Muhammadiyah Makassar, 2021)
Problematics of high pregnancy before marriage, abortion case, and divorce in Indonesia, showing that education has not implicated positive for woman character. However, woman is a key of genesis superior prospective in the future. This thing is also realized by Islamic boarding school based on religion dogmas interrelated education for woman. This article examine deeply about concept and implementation of woman education in the tertiary educational institution of Islamic boarding school. Data in this research are collected by method of participant observation, interview and documentation. Then those data are reduced, provided as conceptual to be taken the conclusion. Result of research indicated that woman education in the tertiary educational institution of Islamic boarding school included by three elements: regulation, actor and feedback. This woman education is being on expression values Islamic, Tarbawi and Ma’hadi. By purpose producing Muslim woman who are salihah, qanitah, hafidzah linafsiha, raiyah fi baiti zaujiha, murabbiyah liawladiha dan qa’idah liqaumiha.